Undocumented Saints: The Politics of Migrating Devotions - Calvo-Quiros, William A. (Oxford University Press, 2022)
UnDocumented Saints follows the migration of popular saints from Mexico into the United States and the evolution in their meaning. The book explores how Latinx battles for survival are also performed in the worlds of faith, religiosity, and the imaginary and how the sociopolitical realities of exploitation and racial segregation frame popular religious expressions. It analyzes the emergence of interreligious states, transnational ethnic and cultural enclaves unified by faith/religiosity. Following a chronological approach, this book analyzes five vernacular saints who have emerged in Mexico and whose devotions have migrated into the United States in the last one hundred years: Jesús Malverde, a popular bandito turned saint caudillo; Santa Olguita, an emerging feminist saint linked to border women’s experiences of sexual violence and assault; Juan Soldado, a soldier who was a murderer and rapist, who was the main suspect in the death of an eight-year-old victim known now as Santa Olguita, and who is now a patron for undocumented immigrants; Toribio Romo, a Catholic priest whose ghost/spirit has been helping people cross the border into the United States since the 1990s; and La Santa Muerte, a controversial personification of the dead who is particularly popular among some LGBTQ migrants. Each chapter contextualizes a particularly popular saint with broader discourses about the construction of masculinity and the state, the long history of violence against Latina and migrant women, female erasure from history, discrimination against non-normative sexualities, and the United States and Mexico’s investment in the control of religiosity within the discourses of immigration in the United States